Chemical Oxidation as an Efficient Alternative for Activated Sludge in Small Communities in Egypt - , Engy El Saka; , Ahmed M. Hassanain (Archives of Current Research International, 2017)
Aims: This research was done in an attempt to evaluate the performance of wastewater treatment plants which apply the chemical oxidation treatment and reasons for its success and failure in some of the small communities in Egypt, compared to conventional activated sludge technologies, without increasing the cost and related burden on the state. Study Design: The results of different wastewater treatment processes were collected, analyzed, and compared to evaluate the efficiency and cost of chemical oxidation wastewater treatment compared to extended aeration and oxidation ditch technology. Methodology: Data collected from the records of wastewater quality tests of the Holding Company for Water and Wastewater for the following Egyptian Governorates Kafr El-Sheikh, EL-Gharbia, EL-Sharqia , El-Monofyia ,Damietta, Red Sea, Suez, South Sinai, and El-Fayoum, Governorates. The measured parameters were BOD, COD, TSS and pH for both the influent and effluent in chemical oxidation, oxidation ditches, and extended aeration treatment plants. Results: The interrelation between removal efficiency and BOD, removal efficiency and COD, removal efficiency and TSSin each studied type of wastewater treatment, graphically represented, analyzed, and discussed in order to recommend the optimum treatment technology with minimum initial and operation cost. Conclusion: The study concluded that the chemical oxidation treatment technology gives an excellent efficiency for the studied wastewater discharges and under the study conditions. The performance of oxidation ditch technology was superior to that of the extended aeration technology was lower than expected, while the oxidation ditches plant showed the lowest performance.